Perbandingan Relational Database dan Non-Relational Database dalam Pengembangan Smart Tourism - Mutmainnah A; Musyrifah Musyrifah; Nuralamsyah Zulkarnaim (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The smart tourism application that is built cannot be separated from the role of the database. The more data stored in a database system, it will affect the speed of access of the information system that uses it. This study will test the performance of query response time between two types of databases with 92 data records of tourist attractions, 106 restaurants and 59 lodging data. Tests were carried out on Data Manipulation Language (DML), aggregate function testing, and logical operator testing. The result of this study is that Non-relational databases are proven to be superior in the DML testing process (insert, select, update, and delete) than Relational Databases. For the process of testing logical operators (AND, OR, and NOT) Non-relational databases are proven to be superior to Relational Databases. In the MIN aggregate function test the results are the same, while the MAX Relational Database aggregate function test is superior to the Non-relational database.